ANALYZING THE EFFECT OF MICRO RUBBER, MICRO SIO2, AND NANO SIO2 IN MICROCRACKS IN SELF-CONSOLIDATING CONCRETE (SEM OBSERVATION) - Ehsan Adili (Civil Engineering Journal, 2021)
The present study is an attempt to analyze the effect of micro rubber waste in self- consolidating concrete (SCC) and to compare the concrete containing SCC with conventional additives such as micro SiO2 and nano SiO2. The use of rubber waste can be substantially important from the environmental point of view. Hence, concrete specimens containing 1, 3 and 5% micro rubber waste were made. Moreover, specimens containing 1, 3 and 5% nano SiO2 and 4, 8 and 12% micro SiO2 were prepared to compare their behaviour and microstructure with each other and with the witness specimens. The effect of the other parameters such as the specimen age and the w/c ratio on the microstructure of concrete containing rubber waste was also studied. Thereafter, the specimens were imaged using a scanning electron microscope (SEM) to observe and compare the microcracks in the concrete and secondary electron beam (SE) was used to obtain their images. The results of the microstructural consideration of different specimens showed that 1% of micro rubber waste can improve the behaviour of self-consolidating concrete, but the concrete microstructure strength and quality decline with an increase in its amount.